Adsorption, regeneration and kinetic of gas phase elemental mercury capture on sulfur incorporated porous carbon synthesized by template method under simulated coal-fired flue gas. (15th June 2023) - Zhou, Qiang; Zhu, Feifei; Gong, Ruhao; Chi, Jihong; Sun, Jiahong; Xu, Guiling; Lu, Ping
Highlights: A SIC was synthesized by template method with excellent mercury capture capability. After multiple cycles of regeneration, the SIC still keeps a mercury capture rate of 90%. Mercury adsorption on SIC has better thermal stability and belongs to chemisorption. Mercury capture product is HgS and after regeneration, the group of C-S-C gets restore. Mercury capture on SIC includes surface adsorption and internal diffusion adsorption. Abstract: A sulfur incorporated porous carbon (SIC) was synthesized by utilizing template method with precursor of 2-thiophene ethanol (C6 H8 OS) and thymol blue (C27 H30 O5 S). Gas phase elemental mercury capture and regeneration capability of the SIC was explored in a fixed-bed experimental system. Mercury capture product on the SIC was studied by using Hg-TPD experiment. The kinetic parameter, activation energy, and mass transfer characteristic of mercury capture by the SIC was analyzed by using different mathematical models to reveal the mechanism of mercury removal. The results show that the SIC displays excellent mercury capture capability under different flue gas component with adsorption product of HgS. Coexistence of SO2 and H2 O in flue gas slightly promotes mercury capture with formation of a small amount of HgSO4 . The SIC also exhibits good regeneration ability that after multiple cycles of mercury capture and regeneration, the SIC still keeps a mercury capture rate of 90%. This is because after thermal regeneration, the group of C-S-C on the SIC gets restore and the adsorbed oxidized sulfur is released. Mercury adsorption on the SIC has better thermal stability compared to traditional activated carbon with an adsorption energy of −62.82 kJ/mol, which belongs to chemisorption. Mercury capture on the SIC is firstly dominated by surface adsorption and then converts to internal diffusion adsorption. External mass transfer is mercury adsorption control step and increase of initial mercury concentration promotes global mass transfer mainly via improvement of internal diffusion rate .